The Reasons for Refusing Kidney Transplantation Among Iranian Patients Undergoing Peritoneal Dialysis - Fateme Biabani; Gholamhossein Mahmudirad; Hadi Hassankhani; Azad Rahmani (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2022)
Background and Objectives:  Kidney transplantation is the safest way to treat chronic renal failure, but for many reasons many patients are reluctant to have a kidney transplant. Identifying these factors can facilitate the transplant process and improve the quality of life of patients undergoing dialysis. Therefore, this study aims to investigate the reasons for refusing kidney transplantation among Iranian patients undergoing peritoneal dialysis (PD). Methods: In this qualitative study, 18 patients with PD were selected from four provinces of Iran using a purposive sampling method. The data were collected by semi-structured interviews and the content were analyzed by a conventional content analysis. Results: Results led to the identification of three main categories: Difficult process, unacceptability of outcome, and familiarization with PD. According to patients, kidney transplantation is a long-term procedure that causes financial stress and physical and social problems and there is a risk of transplant rejection. On the other hand, patients were accustomed to performing PD and considered it a part of their life. Conclusion: Iranian patients undergoing PD have many reasons to refuse kidney transplantation. Full coverage of kidney transplants by the insurance organization, reduction of transplantation time, and provision of medical and psychological counseling can reduce these barriers to accepting kidney transplants by patients.